Peningkatan Kedisiplinan dan Prestasi Belajar Siswa Melalui Penerapan Model Pembelajaran Kooperatif Tipe Student Teams Achievment Division Kelas IV SD Inpres Onekore 6 - Emiliana Nata (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
Type of this research used are Classroom Action Research (CAR), which held in 2 cycles. The subject of this research were 22 student fourth grade of Onekore 6 Primary School. The technical data submission in this research were observation and written test. The research result showed that: 1) the effort to improve student’s discipline and learning achievement in social studies subject by using cooperative learning model STAD type can be done by these steps: teacher convey the learnings, students learn in team, students do the test individually, and teacher giving team’s achievement; 2) the application of cooperative learning model STAD type can improve discipline in social studies subject. This can be seen by the improvement of student’s discipline average score from former condition was 4,95 (low) into 7,89 (medium) in cycle I and into 10,41 (high) in cycle II; and 3) the application of cooperative learning model STAD type can improve social studies achievement. This can be seen by the improvement of student’s average score from former condition is 51,34 into 53,33 in cycle I and into 66,59 in cycle II.The improvement of student’s percentage who reach KKM (63) from former condition was 20% into 22% in cycle I and into 59 % in cycle II .